2002
DOI: 10.1016/s0888-7543(02)96850-3
|View full text |Cite
|
Sign up to set email alerts
|

The Human and Mouse Replication-Dependent Histone Genes

Abstract: The multigene family encoding the five classes of replication-dependent histones has been identified from the human and mouse genome sequence. The large cluster of histone genes, HIST1, on human chromosome 6 (6p21-p22) contains 55 histone genes, and Hist1 on mouse chromosome 13 contains 51 histone genes. There are two smaller clusters on human chromosome 1: HIST2 (at 1q21), which contains six genes, and HIST3 (at 1q42), which contains three histone genes. Orthologous Hist2 and Hist3 clusters are present on mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
149
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 0 publications
2
149
0
1
Order By: Relevance
“…While genetic manipulation of H2B is relatively easy in the yeast, which harbors only two H2B genes and can survive with even a single copy, this is impractical in mammals, whose genomes contain at least 17 H2B genes [60]. A more feasible strategy to investigate the role of H2Bub in mammalian transcription regulation is to deplete the cells of the responsible E3 ligase, RNF20, via RNAi [61].…”
Section: Monoubiquitylated Histone H2bmentioning
confidence: 99%
See 1 more Smart Citation
“…While genetic manipulation of H2B is relatively easy in the yeast, which harbors only two H2B genes and can survive with even a single copy, this is impractical in mammals, whose genomes contain at least 17 H2B genes [60]. A more feasible strategy to investigate the role of H2Bub in mammalian transcription regulation is to deplete the cells of the responsible E3 ligase, RNF20, via RNAi [61].…”
Section: Monoubiquitylated Histone H2bmentioning
confidence: 99%
“…Moreover, Minsky et al [53] demonstrated that H2Bub is selectively associated with the transcribed regions, but not the promoters, of expressed genes. These observations do not necessarily imply an active role for H2Bub in mammalian transcription regulation; nevertheless, such a role can be deduced from earlier studies in the budding yeast, where the use of strains harboring a point mutation in the ubiquitylation site of H2B revealed the direct involvement of H2Bub in transcriptional regulation [40,58,59].While genetic manipulation of H2B is relatively easy in the yeast, which harbors only two H2B genes and can survive with even a single copy, this is impractical in mammals, whose genomes contain at least 17 H2B genes [60]. A more feasible strategy to investigate the role of H2Bub in mammalian transcription regulation is to deplete the cells of the responsible E3 ligase, RNF20, via RNAi [61].…”
mentioning
confidence: 99%
“…H2a genes (see Marzluff et al 2002 for a more detailed description). Since specific nuclear transport elements have previously been identified in the mouse H2a-614 mRNA (Huang and Carmichael 1997), we chose this mRNA as a model substrate for examining histone mRNA export.…”
Section: Introductionmentioning
confidence: 99%
“…The expression patterns of H3.3 coding genes In the human species, the genes encoding H3.1 and H3.2 lack introns and do not have a polyA signal, though they contain a palindromic termination element, which is involved in the regulation of transcriptional termination (Marzluff et al, 2002). Ten H3.1 genes have been identified (HIST1H3A to HIST1H3J), all of which are located in the histone cluster 1 on chromosome 6p22-p21.3 (Marzluff et al, 2002).…”
Section: The Properties Of H33 Compared With Its Canonical Counterpartsmentioning
confidence: 99%
“…Ten H3.1 genes have been identified (HIST1H3A to HIST1H3J), all of which are located in the histone cluster 1 on chromosome 6p22-p21.3 (Marzluff et al, 2002). H3.2 is coded by three genes, namely HIST2H3A, HIST2H3C and HIST2H3D on chromosome 1 (Marzluff et al, 2002). These H3 genes are all expressed simultaneously at S phase, together with the other canonical histone genes (Frank et al, 2003).…”
Section: The Properties Of H33 Compared With Its Canonical Counterpartsmentioning
confidence: 99%